Centre-specific differences in short-term outcomes in neonates with hypoxic-ischaemic encephalopathy (Swiss Medical Weekly, 2021)
AIMS OF THE STUDYTo investigate and compare the centre-specific short-term outcome indicators seizures, arterial hypotension, infection and mortality during therapeutic hypothermia until discharge from the neonatal/paediatric intensive care unit in term and near-term neonates with hypoxic-ischaemic encephalopathy (HIE) registered in the Swiss National Asphyxia and Cooling Register between 2011 and 2018.METHODSRetrospective analysis of prospectively collected national register data between 1 January 2011 and 31 December 2018. Pregnancy, maternal, delivery and neonatal characteristics were compared between the centres. Four short-term outcomes were defined: seizures, arterial hypotension, infection and mortality. The outcome indicators were defined as stated in the protocol of the Swiss National Asphyxia and Cooling Register. Descriptive analyses of the de-identified centre to centre analysis were performed, and standardised observed-to-expected values (risk adjusted for male sex, small for gestational age, Sarnat score on admission, pregnancy/delivery complications) of each centre were compared using with the entire network indirectly standardised mortality/morbidity ratio charts.RESULTS570 cooled neonates with HIE receiving therapeutic hypothermia in 10 different centres were included. Clinical or subclinical seizures were reported in a median of 32% (range 17–49%). Arterial hypotension occurred in a median of 62% (range 30–90%). Median infection rate was 10% (range 0–31%). Median mortality rate until discharge was 14% (range 0–25%).CONCLUSIONSShort-term outcome indicators of seizures, arterial hypotension, infection and mortality showed significant differences in incidence between the centres. These data will help to establish benchmarks for the assessed outcome measures. Benchmarking is a continuous need with the ultimate goal of improving modifiable short-term outcomes in neonates with HIE.